112k views
2 votes
B. Factorize using middle term break 3d2 - 16dc – 12c2

2 Answers

4 votes

Answer:

= 3d² - (18 - 2 )dc - 12c²

= 3d² - 18dc - 2dc - 12c²

= 3d( d - 6c) - 2c( d - 6c)

= ( d - 6c) ( 3d - 2c)

Explanation:

User Resu
by
5.3k points
3 votes

Explanation:

Given

3d² - 16dc - 12c²

Using middle term break

= 3d² - (18 - 2 )dc - 12c²

= 3d² - 18dc - 2dc - 12c²

= 3d( d - 6c) - 2c( d - 6c)

= ( d - 6c) ( 3d - 2c)

Hope it helps and have a great day onwards

User Ojdo
by
4.7k points